The Multi-Omics Analysis of Key Genes Regulating EGFR-TKI Resistance, Immune Infiltration, SCLC Transformation in EGFR-Mutant NSCLC - Wang Z; Zhang L; Xu W; Li J; Liu Y; Zeng X; Zhong M; Zhu Y (Dove Medical Press, 2022)
Zhi Wang,1 Lingling Zhang,1 Wenwen Xu,1 Jie Li,1 Yi Liu,1 Xiaozhu Zeng,1 Maoxi Zhong,1 Yuxi Zhu1,2 1Department of Oncology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400042, People's Republic of China; 2Department of Oncology, Jinshan Hospital of the First Affiliated Hospital of Chongqing Medical University, Chongqing, 400042, People's Republic of ChinaCorrespondence: Yuxi Zhu, Tel +86-23-88955813, Fax +862368811487, Email zhuyuxi@hospital.cqmu.edu.cnBackground: Lung cancer is a high-risk malignancy worldwide. The harboring of epidermal growth factor receptor (EGFR) mutations in non-small cell lung cancer (NSCLC) makes EGFR-tyrosine kinase inhibitor (EGFR-TKI) an attractive therapeutic option. However, patients usually suffer the primary and secondary resistance to EGFR-TKI. And the molecular alteration is still not fully clear and needs further study.Methods: The GEO database was utilized to find the differentially expressed genes (DEGs) in NSCLC profiles resistant to the 1st or 2nd generation EGFR-TKI. We analyzed the expression and pathway enrichment of hub genes, and the prognosis of EGFR mutant/wild-type lung adenocarcinoma (LUAD). Moreover, small cell lung cancer (SCLC) and TKI-resistant profiles were used to find common DEGs, and construct miRNA regulatory network. Analysis was performed of hub genes' related immune infiltration, drug sensitivity, and methylation. Further, we analyzed hub gene expression in EGFR-mutant LUAD and paracancerous tissue by qRT-PCR.Results: A total of 107 DEGs were found related to TKI resistance. Eleven hub genes were obtained after visualization, of which 5 hub genes were co-expressed in SCLC with common miRNAs. Lower expression of SPP1 (hub gene) was associated with better survival in NSCLC. The immune infiltration analysis showed more CD4+ T cells in the resistant group with high expression of SPP1. SPP1 and CD44 promoters' methylations were independent prognostic factors of LUAD. And the expression level of SPP1 related to the sensitivity of EGFR-TKIs in multiple cancer cell lines. qRT-PCR validated the higher expression of SPP1 in EGFR-mutant LUAD than in normal tissue.Conclusion: Our study suggested that the upregulation of SPP1 might induce resistance to the 1st and 2nd generation EGFR-TKI, and influence tumor immune infiltration, resulting in poor survival. ZEB1, SPP1, MUC1, CD44, and ESRP1 might be molecular drivers of SCLC transformation of TKI resistance.Keywords: bioinformatics analysis, drug resistance, epidermal growth factor receptor, non-small cell lung cancer, small cell lung cancer transformation, immune cell infiltration